2012
DOI: 10.1016/j.eurpsy.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of cannabis use disorders in adolescents with early onset first episode psychosis

Abstract: Baseline CU was associated with worse baseline characteristics, but only persistent CU was linked with worse outcome. About half of those with baseline CU reduced cannabis during treatment. For these, effectively treating the psychotic disorder may already be beneficial. However, future research is necessary on the reasons for persistent CU in EOP and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 33 publications
3
58
0
2
Order By: Relevance
“…SUD patients look younger at onset of psychiatric symptoms (Modestin et al, 2001), more frequently male and smokers (Cantor-Graae et al, 2001), unmarried (Farrelly et al, 2007;Wobrock et al, 2007;Mazzoncini et al, 2010) and unemployed (Compton et al, 2009;Barrigón et al, 2010;Schimmelmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SUD patients look younger at onset of psychiatric symptoms (Modestin et al, 2001), more frequently male and smokers (Cantor-Graae et al, 2001), unmarried (Farrelly et al, 2007;Wobrock et al, 2007;Mazzoncini et al, 2010) and unemployed (Compton et al, 2009;Barrigón et al, 2010;Schimmelmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(Cantwell et al, 1999;Veen et al, 2004;Henquet et al, 2005;Mauri et al, 2006;Koskinen et al, 2010;Mazzoncini et al, 2010;Barrigón et al, 2010). Several studies on schizophrenia have reported that patients with SUD have worse premorbid social functioning (Sevy et al, 2010;Mazzoncini et al, 2010;Compton et al, 2011;Schimmelmann et al, 2011), more severe symptoms at onset (Gearon and Bellack, 2000;Dawe et al, 2011), lower compliance and worse treatment response, thus more inappropriate use of mental health services, (Lambert et al, 2005;de Haan et al, 2007;Schimmelmann et al, 2011) with higher mental health costs (Bartels et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…21,25 In the CAFEPS study, adolescent cannabis users were older at baseline and had higher positive and negative syndrome scale (PANSS) positive scores and lower PANSS negative, PANSS general and PANSS total scores than non-users.…”
mentioning
confidence: 99%
“…The increased risk appears to be dose-related and may be greater in those with a family history of schizophrenia. Cannabis is arguably the most serious comorbidity with schizophrenia because of its widespread use among young people with mental illness (Schimmelmann et al, 2012). Cannabis use has a well-recognised role in triggering onset and exacerbations of schizophrenia (Gururajan et al, 2012;Stefanis et al, 2014) and is associated with a worse outcome and reduced efficacy of treatment (Gupta et al, 2013).…”
Section: Psychosis and Substance Usementioning
confidence: 99%